RhGareh® - Welyne, J.J. (University of Malaya, 2015)
Rh.Gareh is an attempt trademark that represents indigenous knowledge of the Iban women weavers in Rumah Garie, Nanga Kain, Sarawak. It was created with the consciousness of traditional intellectual property rights as the underlying and core structure of the productions of the pua kumbu, the Iban traditional textile. The purpose of this trademark is to carry a “fairshare” structure to assist Iban women weavers. The operational cost and raw materials for the pua productions are funded by a pool of capital via a “self-help organisation” in which capital to start of the marketing and selling operations was conceived through the contributions of the weavers and the researcher who are involved in this project. This trademark registered in class 25 and 26